2021
DOI: 10.1039/d0fo03301d
|View full text |Cite
|
Sign up to set email alerts
|

The food additive fast green FCF inhibits α-synuclein aggregation, disassembles mature fibrils and protects against amyloid-induced neurotoxicity

Abstract: α-Synuclein (α-syn) aggregates into cytotoxic amyloid fibrils, which are recognized as the defining neuropathological feature of Parkinson’s disease (PD). Therefore, inhibiting α-syn fibrillogenesis and disrupting the preformed fibrils are both...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…The results of the thioflavin T fluorescence assays also demonstrated that kaempferol reduced the β-sheet content of amyloid fibril formation of α-Syn. Moreover, the TEM results confirmed that the amyloid fibril formation of α-Syn was altered by kaempferol to form a structure resembling an amorphous aggregation that had low cytotoxicity [ 14 , 21 ] or made it more easily degradable by autophagy. Thus, the present results indicate that kaempferol is a candidate prototype for the development of drugs that could prevent the aggregation of amyloid fibril formation of α-Syn in synucleinopathies.…”
Section: Discussionmentioning
confidence: 84%
“…The results of the thioflavin T fluorescence assays also demonstrated that kaempferol reduced the β-sheet content of amyloid fibril formation of α-Syn. Moreover, the TEM results confirmed that the amyloid fibril formation of α-Syn was altered by kaempferol to form a structure resembling an amorphous aggregation that had low cytotoxicity [ 14 , 21 ] or made it more easily degradable by autophagy. Thus, the present results indicate that kaempferol is a candidate prototype for the development of drugs that could prevent the aggregation of amyloid fibril formation of α-Syn in synucleinopathies.…”
Section: Discussionmentioning
confidence: 84%
“…The IC 50 value was negatively correlated to the inhibitory effect on αSN aggregation. The significantly lower IC 50 values for Hst compared to that for previously reported αSN aggregation inhibitors, such as fast green FCF (IC 50 = 37.9 μM), 3-methoxy-4-acetamidoxycinnamic acid (IC 50 = 50.0 μM), and rifampicin (IC 50 = 502.3 μM), indicate that Hst had a better inhibitory effect on αSN fibrillation. Nevertheless, the inhibitory effect of Hst was not as good as that of recognized high-efficiency inhibitors such as epigallocatechin gallate (EGCG) (IC 50 = 4.5 μM) and brazilin (IC 50 = 8.2 μM) (Table ).…”
Section: Results and Discussionmentioning
confidence: 71%
“…For kinetics, the pretreated Aβ 40 (25 μM) monomer was coincubated with ThT iependently or in the presence of different concentrations of TTR or TP. ThT fluorescence was monitored at a regular interval of 10 min at 37 °C to study the fibrillization kinetics with a fluorescence plate reader (Infinite M200 Pro, TECAN, Salzburg, Austria) . The excitation and emission wavelengths of ThT are 440 and 480 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…ThT fluorescence was monitored at a regular interval of 10 min at 37 °C to study the fibrillization kinetics with a fluorescence plate reader (Infinite M200 Pro, TECAN, Salzburg, Austria). 59 The excitation and emission wavelengths of ThT are 440 and 480 nm, respectively. The samples without Aβ 40 were subtracted as the background.…”
Section: ■ Conclusionmentioning
confidence: 99%